El juego didáctico para potenciar el desarrollo cognitivo de los niños de primer grado de educación general básica paralelo “d” sección matutina de la escuela teniente Hugo Ortiz de la ciudad de Loja, periodo 2017-2018 - Sanchez Cuenca, Valeria Alexandra (2018)
This research work, THE EDUCATIONAL GAME TO ENHANCE THE COGNITIVE DEVELOPMENT OF CHILDREN OF FIRST GRADE GENERAL EDUCATIÓN BASIC PARALLEL "D" MORNING SECTION OF THE SCHOOL TENIENTE HUGO ORTIZ OF THE CITY OF LOJA, PERIOD 2017-2018, has as general objective to determine the incidence of educational game to enhance the cognitive development of children, methods, scientific, analytical and synthetic, deductive-inductive and statistical was used, the techniques used were the survey to the teacher to diagnose the existence of the use of the didactic game in the school day and test skills cognitive of the author Dr. Amable Ayora to determine the cognitive development of children. The study sample consisted of 22 children investigated. What you get as a main result in the initial test 12 children representing 54.54% are with low cognitive level, then an activity guide was applied for a period of two month to reevaluate children and the effectiveness of the activities evidenced an improvement in cognitive development of 18 investigated children representing 86.33% with a cognitive very satisfactory development, so it is concluded that the development and implementation of an activity guide educational games is essential to guide the professional in the teaching process based on the educational game to enhance the cognitive area of children, teachers finally recommended to emphasize activities involving the educational game, and apply it daily in each school day to enhance the cognitive development of children.